Predictors of the Effectiveness of Different Approaches to Pandemic Distance Learning - Jiří Kohout; Dana Buršíková; Jan Frank; Jindřich Lukavský; Pavel Masopust; Iva Motlíková; Lucie Rohlikova; Jan Slavík; Václav Stacke; Jana Vejvodová; Michaela Voltrová (MDPI AG, 2022)
Significant attention has been devoted to the forced switch to distance learning as a result of the COVID-19 pandemic. However, some aspects of this issue that are very important for practice are still understudied. The aim of this study is to describe the development of an online-available screening tool which could help the teachers to identify the students at risk of lowered effectiveness during the distance learning and also to select an appropriate teaching approach for the given class. A complex survey involving 35 teachers of Czech language, German language, Mathematics, Physics and Geography, and more than 1400 of their students from 70 classes, was carried out. In the first step, we identified which out of the more than 100 potentially relevant variables have predictive value for the effectiveness of distance learning. Subsequently, a series of multilinear regression models enabling to quantify the impact of the individual variables on effectiveness and perceived usefulness of distance learning were developed. Moderation analysis was also used to model how suitable synchronous and asynchronous activities based on active learning are for classes with different characteristics. Based on the results of the models, a simple screening tool helping teachers to tailor their approach and strategy is being developed.